Correlation between Islamic Religious Education and Student Behavior: Quantitative Study at Singaperbangsa University of Karawang - Muzaki, Iqbal Amar; Mustofa, Taufik; Permana, Hinggil; Nurhasan, Nurhasan; Faizin, Muhamad (UMSU, 2025)
This study examines the correlation between active participation in Islamic Religious Education (PAI) courses and student behavior at Singaperbangsa University in Karawang. The background of this study is based on the importance of character building and positive student behavior in higher education amidst the challenges of the digital era and rapid social change, as well as the role of PAI in the process. The formulation of this research problem is to examine whether there is a positive correlation between students' activeness in attending PAI courses and their behavior. This study used a quantitative approach with survey method and correlational design, involving 81 undergraduate management students of Universitas Singaperbangsa Karawang who took PAI courses. Data were collected through a questionnaire that measured their participation in PAI courses and various aspects of student behavior. The results of the analysis showed a strong and statistically significant positive relationship between active participation in PAI courses and student behavior (r = 0.605, p 0.01). This finding indicates that students who are more active in PAI courses tend to exhibit more positive behaviors. This article contributes to the theoretical understanding of the effectiveness of PAI in shaping student behavior, and provides practical implications for curriculum developers and PAI lecturers to improve the quality of learning to foster positive behavior in students.